‘LISTENING’ AS A RADICAL PRACTICE FOR TRANSFORMATIONAL LEARNING - Connie Guberman (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This paper, under the conference theme of ‘pedagogy,’ will discuss the findings of a qualitative research project that explored the impact of university teaching practices that use life and oral history methodology. The analysis relied on student impact statements as well as instructor assessments. It was conducted over 10 courses that focused on teaching students to conduct life and oral history interviews. The findings of the research demonstrated that focusing on training students to ‘listen’ while gathering stories was as an effective means of developing agency and confidence particularly among women students, while also giving voice to community members often not included in official records. While oral history is not a new methodology, the study found that students experienced it as a most radical practice that held space for inclusive dialogue, self-reflection and a reassessment and reconstruction of dominant stories and narratives. Women and other marginalized peoples’ complex lives have typically been invisible. Providing student researchers with the opportunity to engage directly with community members in retelling their life stories was an opportunity for them to be portrayed in more dynamic and complex ways. It was also a way for students to become active listeners and learners, and to feel inspired to become engaged civic actors in the future. As one student noted, this form of “research gives voice to those who are rarely heard, but have the most important and telling social commentaries to offer… my experience has been amazing… I plan to reach out and hear more voices because I have grown a stronger passion for listening.” Teaching students to ‘listen’ through conducting oral histories is a method that is transferable to learning across disciplines.